MENINGKATKAN MOTIVASI BELAJAR KELOMPOK DENGAN MEDIA WORD WALL MATA PELAJARAN INFORMATIKA KELAS X - Manik Hidayat; Syaad Patmanthara; Manik Hidayat (Universitas Negeri Malang, 2024)
Abstract: This study aims to explore the effectiveness of the Word Wall media in enhancinggroup learning motivation in the subject of Computer Science at the high schoollevel, specifically for tenth-grade students. The Word Wall method is implementedas a collaborative approach that combines interaction between tea chers andstudents with the use of key word visualizations. The study involved X tenth-gradestudents as the sample. The research method employed was classroom actionresearch, utilizing observation, questionnaires, and interviews as data collectioninstruments. The results of the study indicate a significant increase in group learningmotivation following the implementation of the Word Wall media. Studentsdemonstrated more active participation in the learning process, enhancing theirunderstanding of the material, and developing collaborative skills. These findingssuggest that the Word Wall media has the potential to significantly enhance studentlearning motivation in the context of group learning in the Computer Sciencesubject. Practical implications and recommendations for further research arediscussed in the abstract